Management Security of Personality: The Pedagogical Aspect - Kargapoltseva, Natalya A.; Samokhvalova, Anna G.; Kargapoltsev, Sergey M.; Dneprov, Sergey A.; Kuznetsov, Vladimir V. (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the revaluation of values in modern society. The threat of terrorism demands a new look at security as a state of protection of vital interests of person, society and state from internal and external threats. Identity becomes a major object of safety and security of the person's safety is purposeful activities of state and public institutions. The person itself begins to consider security as a public good. The aim of the article is to identify pedagogical aspects of security management of the person. The leading approaches to the study are process and competence-based approaches, allowing considering of the safety of the individual as a process of its protection ensuring and readiness formation for safe behavior. The article reveals the essence and content of personal safety; clarifies external threats to information-psychological security of the personality; gives a comparative analysis of information culture and information competence, as pedagogical conditions of management of information-psychological security of the personality; defines the criteria of information-psychological security of the person (accessibility, pertinence, value, adequacy, security). The paper submissions can be useful for managers and teachers of educational institutions; employees of the centers of advanced training and retraining of personnel in the selection and structuring of the content for the training of scientific and pedagogical staff. Keywords: Security of the Person, Information-Psychological Security, Information Culture, Information Competence. JEL Classifications: I21, I25, I28